Phenolic N-monosubstituted carbamates: Antitubercular and toxicity evaluation of multi-targeting compounds - Krátký, Martin; Janďourek, Ondřej; Baranyai, Zsuzsa; Novotná, Eva; Stolaříková, Jiřina; Bősze, Szilvia; Vinšová, Jarmila (European journal of medicinal chemistry, 2019)
The research of novel antimycobacterial drugs represents a cutting-edge topic. Thirty phenolic N-monosubstituted carbamates, derivatives of salicylanilides and 4-chlorophenol, were investigated against Mycobacterium tuberculosis H37Ra, H37Rv including multidrug- and extensively drug-resistant strains, Mycobacterium avium, Mycobacterium kansasii, Mycobacterium aurum and Mycobacterium smegmatis as representatives of nontuberculous mycobacteria (NTM) and for their cytotoxic and cytostatic properties in HepG2 cells. Since salicylanilides are multi-targeting compounds, we determined also inhibition of mycobacterial isocitrate lyase, an enzyme involved in the maintenance of persistent tuberculous infection. The minimum inhibitory concentrations were from ≤0.5 μM for both drug-susceptible and resistant M. tuberculosis and from ≤0.79 μM for NTM with no cross-resistance to established drugs. The presence of halogenated salicylanilide scaffold results into an improved activity. We have verified that isocitrate lyase is not a key target, presented carbamates showed only moderate inhibitory activity (up to 18% at a concentration of 10 μM). Most of the compounds showed no cytotoxicity for HepG2 cells and some of them were without cytostatic activity. Cytotoxicity-based selectivity indexes of several carbamates for M. tuberculosis, including resistant strains, were higher than 125, thus favouring some derivatives as promising features for future development.
Keywords: Phenols; Salicylanilides; buňky Hep G2; salicylanilidy; Mycobacterium tuberculosis; Carbamates; Carbamate; tuberkulóza; Hep G2 Cells; Cytotoxicity; fenoly; karbamáty; Antitubercular Agents; Humans; isocitrátlyasa; Salicylanilide; Tuberculosis; Isocitrate Lyase; Antimycobacterial activity; lidé; Multi-targeting; antituberkulotika